2020
DOI: 10.1364/oe.388158
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral imaging for high-throughput, spatially resolved spectroscopic scatterometry of silicon nanopillar arrays

Abstract: Modern high-throughput nanopatterning techniques, such as nanoimprint lithography, make it possible to fabricate arrays of nanostructures (features with dimensions of 10’s to 100’s of nm) over large area substrates (cm2 to m2 scale) such as Si wafers, glass sheets, and flexible roll-to-roll webs. The ability to make such large-area nanostructure arrays (LNAs) has created an extensive design space, enabling a wide array of applications including optical devices, such as wire-grid polarizers, transparent conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…While certain applications require the full acquired spectra [23], oftentimes it is convenient to convert the hyperspectral data to an RGB image. RGB images are much more compact, which significantly reduces compute cost.…”
Section: Methodsmentioning
confidence: 99%
“…While certain applications require the full acquired spectra [23], oftentimes it is convenient to convert the hyperspectral data to an RGB image. RGB images are much more compact, which significantly reduces compute cost.…”
Section: Methodsmentioning
confidence: 99%
“…2 A similar study confirmed the possibility of identifying the size of the nanometer structure constituting the semiconductor as a large-area image. 3 Hyperspectral imaging, which acquires signals with both spatial and spectroscopic resolution in a large area as shown in Figure 1b, acquires high spectroscopic resolution spectrum in a wide wavelength area in all pixels of the image. In case of our system, ISR builds hyperspectral cube data at a high speed through spectral scanning using a monochromator, and can measure whole wafer individually in unit blocks within about 2 hours.…”
Section: Introductionmentioning
confidence: 99%